Data Journalism in Africa: A Systematic Review - Sackey, Rainbow; Asiamah, Elizabeth Owusu; Osei- Mensah, Belinda (Advances in Social Sciences Research Journal, 2022)
This study examines the state of Data Journalism scholarship within the African context. The analysis is based on 11 published academic articles retrieved from, Google Scholar, and Sage, ResearchGate and Taylor&Francis and a content analysis process obtained from the existing literature. The review reveals that most of the data journalism research on the African continent is empirical and qualitative in nature. More so, the majority of the studies focused on the practice of data-driven journalism by journalists in print newsrooms. This systematic review is a significant contribution to data journalism research in literature. It serves as the first attempt to aggregate the corpus of literature on data journalism within the African context. It specifically exposes scholars to the focus of the current studies on the phenomenon, the theories and methods that have been employed as well as the gaps that are yet to be explored by researchers on the phenomenon.